Legal and Social Aspects of Employment of Disabled Persons in Poland - Kinal, Jaroslaw; Skora, Michal (European Scientific Journal, ESJ, 2017)
This study is an effort to characterize the legal and social aspects of the polish regulations relating to the employment of people with disabilities in sheltered conditions. In Poland, the role of activation of the disabled in the protected labor market performs three types of operations: sheltered workshops, factories professional activity, and social co-operation. Authors discuss the formal requirements to obtain the status, specific rights, and the obligations of employers who are employing the establishment of protected or reinsured activity. The research included in the study was supplemented by an analysis of available statistical data based on the number of operators protected labor market and the number of disabled people employed in these workplaces.